Effects of thermal boundary conditions on magnetically controlled air flow in a pipe. (6th April 2005) - Lu, Shu-Shen; Ozoe, Hiroyuki
Magnetically controlled laminar air flow in a pipe was studied with applying a strong magnet field from the coil placed at the mid-length of the pipe with four kinds of thermal boundary conditions from the wall. Numerical computations were successfully carried out by solving 2-D equations with static pressure boundary condition and with ξ * from 0 to 2 × 10 7, which represents the strength of the magnetic field and heat flux. The results showed that the volume flow rate increased with the strength of the magnetic field for all four cases of boundary conditions studied. From the distributions of the cross-sectional magnetising force along the pipe length, the following various properties were derived, i.e., pressure distribution, velocity, temperature, pressure gradient distribution along the pipe length and overall air flow rate.